Treatment of primary liver cancer using highly-conformal radiotherapy with kv-image guidance and respiratory control - Law, Ada L.Y.; Ng, Wai-Tong; Lee, Michael C.H.; Chan, Augustine T.S.; Fung, Kai-Hung; Li, Francis; Lao, Wai-Cheung; Lee, Anne W.M. (Radiotherapy and oncology, 2012)
To implement a reliable, practical and reproducible treatment procedure, based on in-room kV-image guidance and respiratory control, for liver cancer patients treated with high dose conformal radiotherapy using a commercially available treatment system. CT stimulation was conducted under voluntary breath hold or gating using the Varian Real-time Position Management™ (RPM) System. Treatments were delivered daily under kV image guidance to verify the diaphragmatic or lipiodol-defined tumor position. Thirty-three patients with liver confined hepatocellular carcinoma were treated between May 2006 and Dec 2009. After a median follow-up period of 16.5months (range: 3.5–40.7), all but 2 patients demonstrated radiological tumor regression. Eight patients (24%) achieved complete remission. The median tumor shrinkage was 42% (27–100%). Subsequent in-field tumor progression was observed in only three patients (10%). For the 23 patients with abnormal alpha fetoprotein level, 22 of them showed biochemical response with a median AFP level drop of 78%. The treatment was well tolerated: Grade 3 toxicities occurred in 5 patients (1 leucopenia, 1 elevated liver enzyme and 3 elevated bilirubin level) but there was no grade 4 toxicity or treatment related death. The 1year overall survival rate is 71.7% and median survival time is 17.2months (3.5–40.7months). Excellent treatment results with minimal toxicities could be achieved in a clinical environment with a commercially available highly sophisticated radiotherapy system.